Concrete Jacketing for Strength Enhancement of Square Columns in Corroded Reinforced Concrete Structures - Amalia, Zahra; Mahlil, Mahlil; Ulza, Adrian; Saidi, Taufiq; Aulia, Teuku Budi; Asyifa, Cut Nella (TEKNIK, 2025)
Buildings submerged during the 2004 Aceh tsunami have shown signs of structural degradation, particularly due to corrosion in column reinforcement, raising concerns about reduced seismic performance. This study aims to evaluate the effectiveness of the concrete jacketing method in retrofitting corroded square reinforced concrete columns. Specimens measuring 200 × 200 mm² in cross-section and 580 mm in height were subjected to accelerated corrosion targeting 20% mass loss, followed by axial and lateral loading tests. The results showed that corrosion reduced shear strength by 23.93% compared to non-corroded specimens. However, retrofitted corroded square reinforced concrete column demonstrated a 15.65% increase in strength when the stirrup reinforcement yielded. However, the shear capacity showed a slight decrease compared to the corroded columns without jacketing. This unexpected reduction is attributed to the absence of joint strengthening in the retrofit, which governed the overall shear resistance. These findings highlight the importance of including joint enhancement when applying concrete jacketing for comprehensive structural recovery.